(untitled) (International Journal of Engineering and Computer Science, 2015)
The stimulating work and determining for social mining of web data, the user interest for individual and non-individual reference systems is an important task. The sharing of the knowledge between the web users has become important in measuring the tradition of web data and marking the information in many social websites as per the requirement of the user. This paper provides an alternative method as an online application reference system for the performance analysis of semantic based methodology. It extracts information from various web application sources and social websites. The information is extracted for the different users to take a proper decision (uncertainty, qualitative and quantitative analyses and risk) at a critical stage. The results of services with conservative web search engines are inadequate in the situation (anomalies, security attacks) and simultaneously reducing the service discovery search space with the attention of mathematical/statistical method to brief the text. The data repository is consisting common data which is reached by the process of obtaining data from different web sources. The semantic data is collected from the ontology based data source and draws it to the user with help of query processor constituent. An online reference system is used to make references for a decision making process of the user. The implementation process of this proposed work is helping the experimental process of an online application reference system for the career guidance of a learner.